2013
DOI: 10.1515/jpem-2012-0015
|View full text |Cite
|
Sign up to set email alerts
|

Triptorelin depot stimulation test for central precocious puberty

Abstract: Sixty-minute postinjection depot triptorelin levels of LH can be successfully used to evaluate the efficacy of treatment with this agent. Limits for suppressed levels have been determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Previous studies have shown that the triptorelin stimulation test can substitute for the gonadorelin stimulation test with high diagnostic accuracy [ 18 , 19 ]. However, the reported optimal duration of stimulation test differs among studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the triptorelin stimulation test can substitute for the gonadorelin stimulation test with high diagnostic accuracy [ 18 , 19 ]. However, the reported optimal duration of stimulation test differs among studies.…”
Section: Discussionmentioning
confidence: 99%
“…Logistic analysis was used to investigate other factors, such as cryptorchidism ( 37 , 38 ), testis volume ( 39 , 40 ), and stimulated levels of LH ( 41 ). The results of which showed that none of were affiliated with spermatogenesis outcome.…”
Section: Discussionmentioning
confidence: 99%